Pseudomonas aeruginosa Outbreak in a Neonatal Intensive Care Unit Attributed to Hospital Tap Water. (18th May 2017) - Bicking Kinsey, Cara; Koirala, Samir; Solomon, Benjamin; Rosenberg, Jon; Robinson, Byron F.; Neri, Antonio; Laufer Halpin, Alison; Arduino, Matthew J.; Moulton-Meissner, Heather; Noble-Wang, Judith; Chea, Nora; Gould, Carolyn V.
Abstract : OBJECTIVE: To investigate an outbreak of Pseudomonas aeruginosa infections and colonization in a neonatal intensive care unit. DESIGN: Infection control assessment, environmental evaluation, and case-control study. SETTING: Newly built community-based hospital, 28-bed neonatal intensive care unit. PATIENTS: Neonatal intensive care unit patients receiving care between June 1, 2013, and September 30, 2014. METHODS: Case finding was performed through microbiology record review. Infection control observations, interviews, and environmental assessment were performed. A matched case-control study was conducted to identify risk factors for P. aeruginosa infection. Patient and environmental isolates were collected for pulsed-field gel electrophoresis to determine strain relatedness. RESULTS: In total, 31 cases were identified. Case clusters were temporally associated with absence of point-of-use filters on faucets in patient rooms. After adjusting for gestational age, case patients were more likely to have been in a room without a point-of-use filter (odds ratio [OR], 37.55; 95% confidence interval [CI], 7.16–∞). Case patients had higher odds of exposure to peripherally inserted central catheters (OR, 7.20; 95% CI, 1.75–37.30) and invasive ventilation (OR, 5.79; 95% CI, 1.39–30.62). Of 42 environmental samples, 28 (67%) grew P. aeruginosa . Isolates from the 2 most recent case patients were indistinguishable by pulsed-field gel electrophoresis from water-related samples obtained from these case-patient rooms. CONCLUSIONS: This outbreak was attributed to contaminated water. Interruption of the outbreak with point-of-use filters provided a short-term solution; however, eradication of P. aeruginosa in water and fixtures was necessary to protect patients. This outbreak highlights the importance of understanding the risks of stagnant water in healthcare facilities. Infect Control Hosp Epidemiol 2017;38:801–808